Improving Cancer Therapy: Design, Synthesis, and Evaluation of Carboplatin-Based Nanoliposomes against Breast Cancer Cell Lines - Hadisadegh, Seyedeh Negin; Ghanbarikondori, Parizad; Sedighi, Armin; Afyouni, Iman; Javadpour, Nikoo; Ebadi, Mehrnoosh (Asian Pacific Journal of Cancer Biology, 2024)
Objective: Cancer poses a significant challenge to modern medicine, with breast carcinoma being one of the most prevalent forms of the disease. Carboplatin is a commonly used chemotherapy drug for treating breast cancer, but its efficacy can be limited due to its poor water solubility and associated side effects. This study intended to enhance the therapeutic potency of carboplatin by encapsulating it within liposomal nanocarriers. Methods: We fabricated nanoscale liposomes loaded with carboplatin via a technique called reverse phase evaporation, and examined their physical attributes. We also studied the toxicity of these nanoliposomes on MDA-MB 231 breast cancer cells. Results: Our findings indicated that the liposomal nanoparticles possessed a negative zeta potential of -18.2 mV and an average size of 278 nm. The drug loading level was 2.2%, while the efficiency of drug encapsulation reached 58.5%. Of note, the cytotoxicity of carboplatin in its nanoliposomal form was markedly more potent against the MDA-MB 231 breast cancer cell line than the free drug (p-value less than 0.05). Conclusion: Our findings suggest that carboplatin-loaded liposomal nanocarriers could potentially serve as an advanced chemotherapeutic approach for the treatment of breast cancer, offering enhanced efficacy and reduced side effects compared to conventional carboplatin therapy. Further research is warranted to explore this novel delivery system’s benefits fully.